Penggunaan Abu Bata Ringan Dengan Penambahan Bentonite Terhadap Kuat Tekan Bebas Dan Kuat Geser Pada Tanah Lempung - Lembang, Michael Tangke; Setiawan, Arman; Yunianti, Nurhadijah (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
Clay soil is a type of basic soil for a structure or construction that has characteristics, namely poor bearing capacity, this makes clay soil a material that is very lacking for construction work, so that improvements are needed by adding additives such as lightweight brick ash and Bentonite to the original soil. This study aims to obtain changes in the value of free compressive strength and shear strength with the addition of lightweight brick ash and Bentonite. With the addition of 10% bentonite, there was an increase of 12.19%, the free compressive strength value of the original soil was 0.812, increasing to 0.911 and the free compressive strength value continued to increase when lightweight brick ash was added with variations of 5%, 10%, 15% and, 20%. According to ASSHTO, the soil is classified as a type of clay soil that is included in group A-7-5, and according to USCS, the soil is included in the OH group "organic clay with moderate to high plasticity". The results of the compaction mechanical properties test increased in the optimum water content and dry volume weight, while the shear strength test obtained an increase in the cohesion value and internal friction angle. The highest cohesion value in the original soil of 10% light brick ash + 20% Bentonite is 0.6143 kg/cm3, and the highest friction angle value in the original soil of 10% light brick ash + 20% is 24.11. Meanwhile, in the compressive strength test, the highest Qu value was found in original soil with 10% light brick ash + 10% Bentonite, namely 1.260.